2016
DOI: 10.3748/wjg.v22.i43.9562
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of incidental branch-duct intraductal papillary mucinous neoplasms of the pancreas: A study with magnetic resonance imaging cholangiopancreatography

Abstract: AIMTo investigate the type and timing of evolution of incidentally found branch-duct intraductal papillary mucinous neoplasms (bd-IPMN) of the pancreas addressed to magnetic resonance imaging cholangiopancreatography (MRCP) follow-up.METHODSWe retrospectively evaluated 72 patients who underwent, over the period 2006-2016, a total of 318 MRCPs (mean 4.4) to follow-up incidental, presumed bd-IPMN without signs of malignancy, found or confirmed at a baseline MRCP examination. Median follow-up time was 48.5 mo (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[54][55][56] MRI/magnetic resonance cholangiopancreatography (MRCP), however, is considered by many as the standard modality for diagnosing a BD-IPMN, with a sensitivity of up to 88%. 53,[57][58][59][60] MRI/MRCP is superior to CT in its ability to identify MPD connectivity and features of malignancy. Furthermore, complementing MRCP with secretin stimulation can elucidate pancreatic ductal anatomy.…”
Section: Diagnostic Methods Of Evaluating Bd-ipmn Patientsmentioning
confidence: 99%
“…[54][55][56] MRI/magnetic resonance cholangiopancreatography (MRCP), however, is considered by many as the standard modality for diagnosing a BD-IPMN, with a sensitivity of up to 88%. 53,[57][58][59][60] MRI/MRCP is superior to CT in its ability to identify MPD connectivity and features of malignancy. Furthermore, complementing MRCP with secretin stimulation can elucidate pancreatic ductal anatomy.…”
Section: Diagnostic Methods Of Evaluating Bd-ipmn Patientsmentioning
confidence: 99%
“…Several studies have reported that those factors included cystic features (cyst size, the presence of a mural nodule, MPD dilatation, and growth rate in size) and patient's factors (symptoms, diabetes mellitus, smoking, or obesity). However, few data are available on risk factors of imaging progression in low‐risk BD‐IPMN . Gausman et al concluded that an initial cyst size ≥2 cm, multifocality of cystic lesions, the patient's past history of prostate cancer, and of smoking could independently predict the onset of new worrisome features.…”
Section: Discussionmentioning
confidence: 99%
“…Gausman et al concluded that an initial cyst size ≥2 cm, multifocality of cystic lesions, the patient's past history of prostate cancer, and of smoking could independently predict the onset of new worrisome features. However, Girometti et al reported that the clinical or baseline features of images under MRCP did not predict imaging evolution or the development of alert findings. The well‐known risk factors for pancreatic cancer include IPMN as well as smoking, diabetes mellitus, a family history of pancreatic cancer and obesity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations